The Power of Media: Exploring the Dynamics of Media Effects on Public Opinion Formation - Muhammad Ehsan Elahi; Amada; Muhammad Waqar; Muhammad Usman (Indus Journal of Social Sciences, 2023)
Background: This research study explored the dynamics of media effects on public opinion formation. Aims: To enhance our understanding of the power of media in shaping individuals' opinions and attitudes. Methods: A multi-method approach was employed, incorporating qualitative and quantitative research methods such as content analysis, surveys, experimental studies, interviews, focus groups, and secondary data analysis. Through these methods, the research examined participants' media consumption habits, perceived impact of media messages, understanding of framing and bias, and the relationship between media exposure and attitude change. Results: The survey results indicated that a majority of respondents (64%) believed that media played a significant role in shaping their opinions. Thematic analysis of qualitative data revealed key themes, including the reliance on social media for news updates (74%), the perceived influence of media on personal opinions (41%), the recognition of media framing techniques (33%), and the perception of media bias (80% of participants). Furthermore, experimental studies demonstrated that participants exposed to high levels of media content experienced a substantial change in attitudes (mean change of 0.8), compared to those with low media exposure (mean change of 0.2) and the control group (mean change of 0.1). Conclusion: Overall, this study provided valuable insights into the influence of media on public opinion formation and underscored the importance of media literacy in navigating the media landscape. However, excessive media exposure lead to the negative shift towards attitude.